Colon classification theory and practice: a self instructional manual - Raju, A A N (New Delhi Ess Ess, 2001)
The Colon Classification (CC)is truly the first faceted scheme for library books classification devised by Dr.S.R.Ranganathan. This work is to present theory and practice of Colon Classification in self-instructional mode.Keeping in view the requirements
Keywords: Classification, Colon; Classification-Books; Classification, faceted